Inflammation and structural changes in the airways of patients with primary Sjögren's syndrome - AMIN, K.; LÚDVÍKSDÓTTIR, D.; JANSON, C.; NETTELBLADT, O.; GUDBJÖRNSSON, B.; VALTYSDÓTTIR, S.; BJÖRNSSON, E.; ROOMANS, G.M.; BOMAN, G.; SEVÉUS, L.; VENGE, P. (Respiratory medicine, 2001)
The present study aimed to compare the cellular pattern and structural changes in the airways of patients with primary Sjögren's syndrome (pSS) with healthy controls. Bronchial biopsy specimens were obtained from seven subjects with pSS and seven healthy controls. All the patients with pSS had increased bronchial responsiveness to methacholine. In the biopsies inflammatory cells, cytokine-producing cells, tenascin and laminin were visualized by immunostaining. Patients with pSS had a higher number of neutrophils and mast cells than healthy controls, while the number of eosinophils was similar in the two groups. The number of IL-8-positive cells was higher in pSS but the numbers of IL-4-and IL-5-positive cells were not significantly different between pSS and healthy controls. The numbers of T cells in patients with pSS were higher than in healthy controls, while the numbers of CD25-positive cells were similar to the healthy controls. The degree of epithelial integrity in patients with pSS was significantly lower than in the control group and the tenascin and laminin layers were significantly thicker in the pSS group. There was a correlation between the number of mast cells and the thickness of the tenascin and laminin layers in pSS. In conclusion, we found that the cellular pattern in the bronchial mucosa of patients with pSS displayed large numbers of neutrophils, mast cells and T-lymphocytes. These changes in inflammatory cell numbers seemed to relate to the observed increased epithelial damage and structural changes of the subepithelium. The structural findings, but not the pattern of inflammatory cells, are shared with atopic asthma and may relate to the increased bronchial hyper-responsiveness seen in both diseases.